MEASUREMENT OF CUSTOMER SATISFACTION INDEX ON SERVICE SATISFACTION AT SAMUDRA SUPERMARKET, MADIUN CITY - Fachmi Al Faroqi; Sena Atmaja; Abu Naim; Dadang; Helmas Septiyo Hadi; Siti Maesaroh (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The retail industry, in this case supermarkets, is one of the places for transactions of the needs and desires of the community facing competition challenges from both online marketplaces and similar offline retail. One of the things that supermarket management pays attention to is customer satisfaction, which is the main goal of the company to increase sales growth. The purpose of this research is to determine the calculation of the customer satisfaction index regarding service satisfaction at Swalayan Samudra in Madiun City. The research method uses quantitative. The data collection method uses a questionnaire instrument. The data analysis technique used the Customer Satisfaction Index (CSI). The research results were concluded based on the satisfaction level criteria table according to the CSI score, which showed a figure of 78%, indicating that customers were satisfied with the quality of the services received.